Game Online menjadi Penyebab Krisis Etika Generasi Muda - Putri, Risma Amalia; Ardhi, Pandji; Haliza, Farah (STMIK BINA PATRIA, 2023)
AbstractÂ Online games are games that are played at one time in real time. Most of the online game enthusiasts are teenagers. This research discusses the relationship between ethics and online games with the aim of finding out the relationship between the influence of online games on the ethics of the younger generation, which is now increasingly diminishing. This research was conducted to realize the negative impact of online games and find solutions to overcome the identity crisis of young people caused by online games. The method used in this research is the library research method, namely a method where data collection is carried out by collecting data from various literature. Several literatures state that online games influence ethics and have positive and negative impacts on the younger generation. The results of our research show that the younger generation is experiencing an ethical crisis which is affecting the psychology of the younger generation. The solution that can be given is to involve parents by setting time limits for playing games.Keywords : Digital, Game Online, EthicsÂ